2002
DOI: 10.4049/jimmunol.169.6.3085
|View full text |Cite
|
Sign up to set email alerts
|

DNA Alkylating Agents Alleviate Silencing of Class II Transactivator Gene Expression in L1210 Lymphoma Cells

Abstract: MHC class II (Ia) Ag expression is inversely correlated with tumorigenicity and directly correlated with immunogenicity in clones of the mouse L1210 lymphoma (1 ). Understanding the mechanisms by which class II Ag expression is regulated in L1210 lymphoma may facilitate the development of immunotherapeutic approaches for the treatment of some types of lymphoma and leukemia. This study demonstrates that the variation in MHC class II Ag expression among clones of L1210 lymphoma is due to differences in the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…DNA methylation is known to be involved in the regulation of CIITA and MHC gene expression in several tumour cell types, including trophoblast-derived cells, a subset of lymphoma cells, and squamous cell carcinoma (Morris et al, 2000;Nie et al, 2001;Murphy et al, 2002;Moreau et al, 2003). Our results suggest that DNA methylation of CIITA-PIV is also a major cause of HLA-DR suppression in haematopoietic tumour cells, especially those derived from T-cells and myeloid cells.…”
Section: Discussionmentioning
confidence: 59%
“…DNA methylation is known to be involved in the regulation of CIITA and MHC gene expression in several tumour cell types, including trophoblast-derived cells, a subset of lymphoma cells, and squamous cell carcinoma (Morris et al, 2000;Nie et al, 2001;Murphy et al, 2002;Moreau et al, 2003). Our results suggest that DNA methylation of CIITA-PIV is also a major cause of HLA-DR suppression in haematopoietic tumour cells, especially those derived from T-cells and myeloid cells.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the inability to induce MHCII expression in response to IFN-+ is often associated with tumor cells of non-hematopoietic origin [58,[95][96][97][98][99][100]. There is growing evidence that this inability to express MHCII results from epigenetic silencing of the MHC2TA gene [95][96][97][98][99][100][101][102]. The regulatory regions of the MHC2TA gene have been found to be hypermethylated at CpG dinucleotides in MHCII -T cell leukemias, B cell lymphomas and various tumor cells that are unable to express MHCII upon exposure to IFN-+ , including teratocarcinoma, choriocarcinoma, neuroblastoma, erythroleukemia and small cell lung cancer [95,97,[100][101][102].…”
Section: Ciita Silencing In Tumor Cellsmentioning
confidence: 99%
“…There is growing evidence that this inability to express MHCII results from epigenetic silencing of the MHC2TA gene [95][96][97][98][99][100][101][102]. The regulatory regions of the MHC2TA gene have been found to be hypermethylated at CpG dinucleotides in MHCII -T cell leukemias, B cell lymphomas and various tumor cells that are unable to express MHCII upon exposure to IFN-+ , including teratocarcinoma, choriocarcinoma, neuroblastoma, erythroleukemia and small cell lung cancer [95,97,[100][101][102]. Histone deacetylation rather than DNA hypermethylation has been implicated in silencing of MHC2TA expression in several squamous cell carcinoma cell lines [103].…”
Section: Ciita Silencing In Tumor Cellsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] For example, in mouse lymphoma cells, DNA-alkylating agents alleviate silencing of class II transactivator gene. 12 Another possible mechanism could be the upregulation and/or neoexpression of costimulatory molecules or cytokines by tumor cells. For example, Mokyr and co-workers 13,14 showed that in the MOPC-315 mouse plasmacytoma, melphalan, mitomycin, and g-irradiation enhanced CD80, INF-b, and TNF-a expression.…”
Section: Introductionmentioning
confidence: 99%